Ертөнцийн үндэстний зураглал (Монгол, орос, англи хэлний идээ, ундааны нэрийн баримтаар зэрэгцүүлэх нь): The National Language Mapping (Comparison of names of food and beverages in the Mongolian, Russian, and English languages) - G., Ganzul (Mongolian Journal of Foreign Languages and Cultures, 2023)
Language is a reflection of reality, preservation, and promotion of national culture. The concept of vocabulary is an integral part of cognition and a result of human cognition and connected to accumulated comprehensive knowledge. Therefore, lexicons can be an informative source of a certain country. Every nation has its environment to live in, style to use something, experience, culture, and tradition, and they have their own words, and phrases to express them. It’s obvious that people observe what is around them and recognize the objects that they have seen before. As a result of this, citizens of any nation mark them with words and give names on what they have learned. Thus, for centuries it has been a national feature in the public consciousness, and the phenomenon has retained as certain patterns and images. These retained images, patterns, ways of life, events, and historical chronological orders are absorbed in languages, and speakers, representatives of any countries express them in their own tongue phonology, dialects, and language. In this article, we tried to explain the concept of global image through the comparison of names of three different types of food and beverages in the examples of Mongolian, Russian, and English languages.